2015
DOI: 10.1038/srep11394
|View full text |Cite
|
Sign up to set email alerts
|

Circulating interleukin-6 and cancer: A meta-analysis using Mendelian randomization

Abstract: Interleukin-6 (IL-6) plays a contributory role in the progression and severity of many forms of cancer; it however remains unclear whether the relevance between circulating IL-6 and cancer is causal. We therefore meta-analyzed published articles in this regard using IL-6 gene -174G/C variant as an instrument. Seventy-eight and six articles were eligible for the association of -174G/C variant with cancer and circulating IL-6, respectively. Overall analyses failed to identify any significance between -174G/C and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 90 publications
(96 reference statements)
0
19
0
Order By: Relevance
“…IL‐6 released from T cells can induce proliferation and differentiation of B cells, as well as stimulate antibody production. Recent studies have revealed that the expression of IL‐6 in primary liver cancer was dramatically elevated and is positively correlated with morbidity and progression . IL‐6 exerts its biological effects through binding to two subunits of signal transducing receptor GP130 and IL‐6R, resulting in dimerization of GP130 and IL‐6R and subsequently activation of the Janus kinases/STAT3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…IL‐6 released from T cells can induce proliferation and differentiation of B cells, as well as stimulate antibody production. Recent studies have revealed that the expression of IL‐6 in primary liver cancer was dramatically elevated and is positively correlated with morbidity and progression . IL‐6 exerts its biological effects through binding to two subunits of signal transducing receptor GP130 and IL‐6R, resulting in dimerization of GP130 and IL‐6R and subsequently activation of the Janus kinases/STAT3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…First, in a panel of 6 plasma biomarkers measured in the INSIGHT SMART study, these 3 biomarkers were strongly associated with all-cause mortality, which motivated us to determine these markers also for the ESPRIT and SILCAAT trials, using stored baseline plasma specimens. [ 6 ] Second, higher levels of IL-6, hsCRP and D-dimer have been associated with increased risk of CVD, cancer, and all-cause mortality among people living with HIV [ 5 11 ], as well as in the general population [ 14 25 , 27 29 ]. Third, the biomarkers have high laboratory and biological reproducibility.…”
Section: Methodsmentioning
confidence: 99%
“…While ART decreases IL-6, D-dimer and hsCRP levels [ 10 , 12 ], these biomarkers remain elevated relative to the general population even when the plasma HIV RNA is suppressed [ 13 ]. Markers of inflammation and coagulation have been widely studied in the general population, and related to higher risk of CVD [ 14 22 ], cancer [ 23 25 ], kidney function decline [ 26 ] and all-cause mortality [ 27 29 ]. These data collectively suggest that chronic inflammation and/or hyper-coagulation contribute to the pathogenesis of these serious non-AIDS events during otherwise effective ART.…”
Section: Introductionmentioning
confidence: 99%
“…Increased expression of IL-6 is thought to act as a link between chronic inflammation and tumor development [ 44 ]. IL-6 stimulates the progression of colon and liver cancers and elevated IL-6 levels are associated with poor prognosis in liver and colon cancers [ 45 47 ]. IL-6 stimulates STAT3 phosphorylation and nuclear translocation of STAT3 to promote oncogenesis by inhibiting apoptosis.…”
Section: Discussionmentioning
confidence: 99%